At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
- a) 66, b) - 1, c) - 20
Step-by-step explanation:
Solve as below
a) a² + ab with a = 6.6, b = 3.4;
- a² + ab = a(a + b) = 6.6(6.6 + 3.4) = 6.6(10) = 66
b) x² - xu at x = 0.5, y = 2.5;
- x² - xu = x(x - u) = 0.5(0.5 - 2.5) = 0.5(- 2) = - 1
c) -5a² - 5ah at a = 4, h = -3;
- -5a² - 5ah = - 5a(a + h) = - 5(4)(4 - 3) = - 20(1) = - 20
Answer:
- a) 66
- b) -1
- c) -20
Step-by-step explanation:
a) a² + ab = ?
→ (6.6)² + (6.6 × 3.4)
→ 43.56 + 22.44
→ 66
So, the answer is 66.
b) x² - xu = ?
→ (0.5)² - (0.5 × 2.5)
→ 0.25 - 1.25
→ -1
So, the answer is -1.
c) -5a² - 5ah = ?
→ -5(4)² - 5(4 × -3)
→ (-5 × 16) - (5 × -12)
→ -80 + 60
→ -20
So, the answer is -20.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.